Oral Hydrogen-Rich Water Alleviates Oxalate-Induced Kidney Injury by Suppressing Oxidative Stress, Inflammation, and Fibrosis - Si, Yachen; Liu, Lulu; Cheng, Jin; Zhao, Tingting; Zhou, Qi; Yu, Jianpeng; Chen, Wei; Ding, Jiarong; Sun, Xuejun; Lu, Hongtao; Guo, Zhiyong (Frontiers in Medicine, 2021)
Objective: To explore the theraputic effects and potential mechanisms of hydrogen-rich water (HRW) against oxalate-induced kidney injury. Methods: The mouse model of Calcium oxalate (CaOx) crystallization was estabolished by feeding a soluble oxalate diet. Crystal deposition, tubular injury, fibrosis and reactive oxygen species (ROS) production in kidneys were examined by histology. Serum indexes of renal injury, inflammation and oxidative stress were detected by commercial kits. RNA sequencing (RNA-seq) was performed to screen potential pathways and the exprssions of key molecules in these pathways were determined by western blotting and immunohistochemistry. Results: Crystal deposition, tubular injury, fibrosis and increased ROS production in kidneys of mice induced by oxalate diet were improved with HRW administration. The indexes of renal injury, inflammation and oxidative stress in serum of mice were upregulated by oxalate diet, which were reduced by HRW. A total of 3566 differential genes were screened by RNA-seq and these genes were analyzed by pathway enrichment and PI3K/AKT, NF-κB and TGF-β pathways were selected for further verification. The expressions of molecules related to PI3K-AKT pathway (PI3K, AKT and p-AKT), NF-κB pathway (NF-κB p65, p- NF-κB p65, NLRP3 and IL-1β) and TGF-β pathway (TGF-β, TGF-βRI, TGF-βRII, p-Smad2 and p-Smad3) in renal tissues were increased by oxalate diet, which were reduced by HRW administration. Conclusion: HRW may alleviate oxalate-induced kidney injury with its anti-oxidative, anti-inflammatory and anti-fibrotic effects via inhibiting PI3K/AKT, NF-κB and TGF-β pathways.